2020
DOI: 10.5312/wjo.v11.i11.528
|View full text |Cite
|
Sign up to set email alerts
|

Use of short stems in revision of standard femoral stem: A case report

Abstract: BACKGROUND Short stems are usually uncemented prosthetics and are recommended in the treatment of traumatic or degenerative diseases of hip. In revision procedures for elderly patients with serious comorbidity, applying a short stem could reduce peri- and post-operative secondary surgical risks to femoral osteotomy, which are necessary for the removal of parts of the implant or acrylic cement from the medullary canal. There are no cases in the literature that apply a short stem for prosthetic revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Evola et al recently published a case report of one patient with stem breakage in the distal part. Intraoperatively, the distal apex of the implant could not be removed easily [7]. In this situation, to avoid a transfemoral approach, extensive operative time associated with increased blood loss and marked soft-tissue damage, a Fitmore short stem (Zimmer; Winterthur, Switzerland) was used.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Evola et al recently published a case report of one patient with stem breakage in the distal part. Intraoperatively, the distal apex of the implant could not be removed easily [7]. In this situation, to avoid a transfemoral approach, extensive operative time associated with increased blood loss and marked soft-tissue damage, a Fitmore short stem (Zimmer; Winterthur, Switzerland) was used.…”
Section: Discussionmentioning
confidence: 99%
“…The 2‑year follow-up resulted in a good clinical outcome with stable implant position. They concluded that short-stem designs can help surgeons to treat specific revision procedures in patients with poor general health conditions to avoid a surgical invasiveness due to transfemoral approaches and long-stemmed revision implants [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations